An Integrative Analysis of Product Differentiation Strategies and Customer Experience in Enhancing Loyalty in the E-Commerce Industry - Agustian, Kresnawidiansyah; Rosadi, Husni Y; Wiwin; Zen, Agustian (ADMAN: Journal of Contemporary Administration and Management, 2024)
The e-commerce industry has undergone significant transformation over the past decades, driven by advances in digital technology and shifts in consumer behavior. Increasingly, consumers are turning to e-commerce platforms to meet their daily needs, from clothing to household goods. This research aims to explore how product differentiation strategies and customer experience can be effectively integrated to enhance customer loyalty in the e-commerce industry. This study employs a literature review method with a qualitative approach. Data for this research is sourced from Google Scholar, with publications limited to the period between 2014 and 2024. Based on the literature review conducted, it can be concluded that product differentiation strategies and customer experience play crucial roles in enhancing customer loyalty in the e-commerce industry. Product differentiation, through innovation, quality, and unique features, can attract customer attention and distinguish a company from its competitors. Meanwhile, a positive customer experience, encompassing the entire shopping journey from product search to after-sales service, can increase satisfaction and foster long-term loyalty.